Family Ownership, Independent Commissioners, Audit Quality, And Tax Avoidance In Indonesia - Nurjanah, Siti; Aligarh, Frank (IAIN Surakarta, 2021)
This study determined the effect of profitability, family ownership, independent commissioners, and audit quality on tax avoidance. This current study analyzed manufacturing companies with family shareholders listed on the Indonesia Stock Exchange from 2017 to 2019. The secondary data used in this study were originated from the companys annual report on its financial statements. The population in this study were all manufacturing companies with family shareholders listed on the Indonesia Stock Exchange from 2017 to 2019. The 35 companies studied were selected using the purposive sampling technique. The analysis technique used was panel data regression using the Eviews 10 program. The results show that profitability has a negative effect on tax avoidance, family ownership has a positive effect on tax avoidance, independent commissioners, and audit quality has no effect on tax avoidance.